Penerapan Metode Problem Based Learning dalam Meningkatkan Pemahaman Adab kepada Teman pada Siswa Kelas 4D MIN 2 Kota Malang - Ardiansyah, Muhammad Rifan (Maliki Interdisciplinary Journal, 2025)
A conducive classroom atmosphere is an important prerequisite in creating an effective learning process. However, in practice, many teachers face challenges in the form of noisy student behavior, especially at the Elementary School level. This study aims to determine the effectiveness of the application of the Problem Based Learning method to improve understanding and attitudes of manners towards friends in class 4D students of MIN 2 Malang City. The problem faced is the lack of student awareness in applying the values ​​of manners to friends in everyday life at school. This classroom action research was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through observation, interviews, documentation, and formative tests. The results of the study showed that the application of the PBL method can improve understanding and behavior of manners towards friends. There was an increase in the average score from 65 in cycle I to 84 in cycle II. In addition, observations showed an increase in students' attitudes in terms of mutual respect, not teasing, and working together in groups. The conclusion of this study is that the Problem Based Learning method is effectively applied in learning Manners to Friends to improve students' understanding and character.